2018
DOI: 10.2478/acph-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of orally disintegrating tablets containing the mosapride resin complex

Abstract: The purpose of this study was to prepare a mosapride citrate-resin (Amberlite® IRP 88) complex and orally fast-disintegrating tablets of the resin complex. The resinate complex of mosapride-Amberlite® IRP 88, mass ratio 2:1, was prepared in an ethanol-water solution. The effects of alcohol concentration, temperature, and pH of the solution on complex formation were evaluated. The complex physicochemical properties were characterized by differential scanning calorimetry, X-ray diffraction and scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Most FD patients present with clinical symptoms including impaired gastric receptivity and delayed gastric emptying, and the factors involved include delayed or rapid gastric emptying as well as hypersensitivity of the viscera, lack of normal regulation of gastric fundus regulation, and coordination disorder of the pylorus and gastric antrum. In the clinical research in terms of sleep, diet, and pressure between FD children and healthy children, it is found that FD children have obviously higher incidence rate of sleep disorders, of which the difficulties in sleep maintenance and falling asleep are the most common; more FD children are eating erratically; and FD children have higher perception of mental stress [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most FD patients present with clinical symptoms including impaired gastric receptivity and delayed gastric emptying, and the factors involved include delayed or rapid gastric emptying as well as hypersensitivity of the viscera, lack of normal regulation of gastric fundus regulation, and coordination disorder of the pylorus and gastric antrum. In the clinical research in terms of sleep, diet, and pressure between FD children and healthy children, it is found that FD children have obviously higher incidence rate of sleep disorders, of which the difficulties in sleep maintenance and falling asleep are the most common; more FD children are eating erratically; and FD children have higher perception of mental stress [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…TCM considers that the disease location of FD is in the stomach, and at the same time, it is associated with viscera such as the liver and spleen. As its pathogenesis lies in the disharmony of the spleen and stomach, TCM mostly focuses on liver soothing, spleen invigorating, and stomach regulating to treat this disease [16,17]. Aiming at the disease mechanism of children, the combination therapy of acupuncture and TCM application was adopted in this study.…”
Section: Discussionmentioning
confidence: 99%